A passage-dependent network for estimating the in vitro senescence of mesenchymal stromal/stem cells using microarray, bulk and single cell RNA sequencing - Yang, Yong; Zhang, Wencheng; Wang, Xicheng; Yang, Jingxian; Cui, Yangyang; Song, Haimeng; Li, Weiping; Li, Wei; Wu, Le; Du, Yao; He, Zhiying; Shi, Jun; et al. (Frontiers in Cell and Developmental Biology, 2023)
Long-term in vitro culture of human mesenchymal stem cells (MSCs) leads to cell lifespan shortening and growth stagnation due to cell senescence. Here, using sequencing data generated in the public domain, we have established a specific regulatory network of “transcription factor (TF)-microRNA (miRNA)-Target” to provide key molecules for evaluating the passage-dependent replicative senescence of MSCs for the quality control and status evaluation of MSCs prepared by different procedures. Short time-series expression miner (STEM) analysis was performed on the RNA-seq and miRNA-seq databases of MSCs from various passages to reveal the dynamic passage-related changes of miRNAs and mRNAs. Potential miRNA targets were predicted using seven miRNA target prediction databases, including TargetScan, miRTarBase, miRDB, miRWalk, RNA22, RNAinter, and TargetMiner. Then use the TransmiR v2.0 database to obtain experimental-supported TFs for regulating the selected miRNA. More than ten sequencing data related to MSCs or MSCs reprogramming were used to validate key miRNAs and mRNAs. And gene set variation analysis (GSVA) was performed to calculate the passage-dependent signature. The results showed that during the passage of MSCs, a total of 29 miRNAs were gradually downregulated and 210 mRNA were gradually upregulated. Enrichment analysis showed that the 29 miRNAs acted as multipotent regulatory factors of stem cells and participated in a variety of signaling pathways, including TGF-beta, HIPPO and oxygen related pathways. 210 mRNAs were involved in cell senescence. According to the target prediction results, the targets of these key miRNAs and mRNAs intersect to form a regulatory network of “TF-miRNA-Target” related to replicative senescence of cultured MSCs, across 35 TFs, 7 miRNAs (has-mir-454-3p, has-mir-196b-5p, has-mir-130b-5p, has-mir-1271-5p, has-let-7i-5p, has-let-7a-5p, and has-let-7b-5p) and 7 predicted targets (PRUNE2, DIO2, CPA4, PRKAA2, DMD, DDAH1, and GATA6). This network was further validated by analyzing datasets from a variety of MSCs subculture and lineage reprogramming studies, as well as qPCR analysis of early passages MSCs versus MSCs with senescence morphologies (SA-β-Gal+). The “TF-miRNA-Target” regulatory network constructed in this study reveals the functional mechanism of miRNAs in promoting the senescence of MSCs during in vitro expansion and provides indicators for monitoring the quality of functional MSCs during the preparation and application.